Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1021/ie058003d
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities and Diffusivities of Carbon Dioxide in Ionic Liquids:  [bmim][PF6] and [bmim][BF4]

Abstract: Gaseous carbon dioxide (CO 2 ) absorption measurements in l-n-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF 6 ]) and l-n-butyl-3-methylimidazolium tetrafluoroborate ([bmim]-[BF 4 ]) were made using a commercial gravimetric microbalance at temperatures of 283.15, 298.15, 323.15, and 348.15 K and at pressures under 2 MPa. Gas solubilities were determined from absorption saturation (equilibrium) data at each fixed temperature and pressure. The experimental solubility data of CO 2 in ionic liquids have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

48
652
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 577 publications
(714 citation statements)
references
References 33 publications
48
652
1
1
Order By: Relevance
“…They used a generic Redlich-Kwong type of cubic EoS [30], with a modified van der Waals-Berthelot mixing rule and critical properties of ILs estimated by Vetere's 4 method [31]. Systems studied by this group include CO 2 in several different Ils [8][9][10][11][12], hydrofluorocarbons and hydrofluoroethers in some Ils [13][14][15][16], ammonia mixtures with Ils [17,18] [23], and H 2 S [24,25]. The authors present most of their results in graphical form and conclude that the model yields a good correlation of the experimental values.…”
Section: Introductionmentioning
confidence: 99%
“…They used a generic Redlich-Kwong type of cubic EoS [30], with a modified van der Waals-Berthelot mixing rule and critical properties of ILs estimated by Vetere's 4 method [31]. Systems studied by this group include CO 2 in several different Ils [8][9][10][11][12], hydrofluorocarbons and hydrofluoroethers in some Ils [13][14][15][16], ammonia mixtures with Ils [17,18] [23], and H 2 S [24,25]. The authors present most of their results in graphical form and conclude that the model yields a good correlation of the experimental values.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of carbon dioxide in a variety of ILs has been determined at low pressures [1][2][3][4][5][6][7][8][9][10] and high pressures (up to 73 MPa) [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In particular, the system (carbon dioxide + [C 1 C 2 Im][NTf 2 ]), also investigated in this work, was studied by several authors [7][8][9][10]14,17].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, Blanchard et al [1] and Aki et al [4] reported vapor-liquid equilibrium data for the system supercritical CO 2 + [bmim][NO 3 ]; Aki et al [4], Kroon et al [7] and Shiflett and Yokozeki [5] studied the system supercritical CO 2 + [bmim] [BF 4 ], while Shiflett and Yokozeki [8] and Shariati et al [6] presented data about the system supercritical CHF 3 + [bmim] [PF 6 ]. All these data show important discrepancies among the different sets.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, Blanchard et al [1], Pérez-Salado Kamps et al [2], Liu et al [3] Aki et al [4], Shiflett and Yokozeki [5] and Shariati et al [6] measured the vapor-liquid equilibrium of the binary system supercritical CO 2 + [bmim][PF6] at different temperatures. In the same way, Blanchard et al [1] and Aki et al [4] reported vapor-liquid equilibrium data for the system supercritical CO 2 + [bmim][NO 3 ]; Aki et al [4], Kroon et al [7] and Shiflett and Yokozeki [5] studied the system supercritical CO 2 + [bmim] [BF 4 ], while Shiflett and Yokozeki [8] and Shariati et al [6] presented data about the system supercritical CHF 3 + [bmim] [PF 6 ].…”
Section: Introductionmentioning
confidence: 99%